2011
DOI: 10.1021/la203492m
|View full text |Cite
|
Sign up to set email alerts
|

Single Kaolinite Nanometer Layers Prepared by an In Situ Polymerization–Exfoliation Process in the Presence of Ionic Liquids

Abstract: A simple chemical route for the exfoliation of kaolinite in the presence of polymerizable ionic liquids and the resulting obtainment of exfoliated nanocomposites is reported. The exfoliation was achieved using three different ionic liquids structurally bearing a vinyl group: 1-methyl-3-(4-vinylbenzyl)imidazolium chloride salt (IL_1), 1-methyl-1-(4-vinylbenzyl)pyrrolidinium chloride (IL_2), and 1-methyl-3-vinyl imidazolium iodide (IL_3) and a urea-kaolinite intercalate as precursor. The reaction was done in one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 62 publications
(70 reference statements)
4
25
0
Order By: Relevance
“…No change in position was observed in the DMSO-kaolinite samples which indicate that the layers remained unaffected which was similarly observed elsewhere (Letaief et al, 2011). However, a broadening was observed that may be attributed to a perturbation of the crystal structure.…”
Section: X-ray Diffractionsupporting
confidence: 76%
“…No change in position was observed in the DMSO-kaolinite samples which indicate that the layers remained unaffected which was similarly observed elsewhere (Letaief et al, 2011). However, a broadening was observed that may be attributed to a perturbation of the crystal structure.…”
Section: X-ray Diffractionsupporting
confidence: 76%
“…These polymerizable ILs (1‐methyl‐3‐(4‐vinylbenzyl) imidazolium chloride salt (IL‐1), 1‐methyl‐1‐(4‐vinylbenzyl) pyrrolidinium chloride (IL‐2), and 1‐methyl‐3‐vinylimidazolium iodide (IL‐3)) were characterized by the presence in their structure of a vinyl group for the polymerization reactions under controlled experimental conditions. In this case, in order to avoid fast and uncontrolled polymerization of the monomers, the intercalation followed by polymerization was performed in one step in isopropanol at 90 °C . The obtained nanocomposite showed complete exfoliation when the urea pre‐intercalate was used for the synthesis.…”
Section: Modification Of Kaolinite By Ilssupporting
confidence: 57%
“…The second step in weight loss ranged from 5.5% to 3.5% with the same abovementioned order. In this step, water is lost due to the thermal dehydroxylation process [21,26,41] or conversion of hydroxide compounds to oxide sample by desorption of water. The weight loss of KB is more than KB-Ca, which indicated grafting of the sulfate group on end capped and surface hydroxyl groups.…”
Section: Thermogravimetric Analysis (Tga) Of Different Catalyst Samplesmentioning
confidence: 99%